2015
DOI: 10.1590/s1679-87592015087106303
|View full text |Cite
|
Sign up to set email alerts
|

Trophic ecology of Mugil liza at the southern limit of its distribution (Buenos Aires, Argentina)

Abstract: In order to get to know the habitat and feeding habits of Mugil liza on the southern coast of Buenos Aires province, 65 specimens obtained at two sampling sites - the San Blas bay (SBB) and the mouth of the Quequén-Salado river (QSR) - during spring (November 2012) and summer (February 2013) were analyzed. Specimens were measured, sexed and weighed, their stomachs were removed and their stomach contents weighed and analyzed under the stereoscopic microscope. The specimens were adults, 28-49 cm in length and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
2
0
4
Order By: Relevance
“…Marine and euryhaline coastal species inhabit dynamic environments so they generally show high plasticity [56], such as atherinids, mugilids and sardines [17,37,[57][58][59]. This plasticity can be reflected in otoliths.…”
Section: Discussionmentioning
confidence: 99%
“…Marine and euryhaline coastal species inhabit dynamic environments so they generally show high plasticity [56], such as atherinids, mugilids and sardines [17,37,[57][58][59]. This plasticity can be reflected in otoliths.…”
Section: Discussionmentioning
confidence: 99%
“…Esta especie M. liza se ha definido como iliófaga, detritívora y capaz de ingerir mayormente diatomeas (Olivera y Soares 1996;Claudino, et al, 2013), y, en consecuencia, caracterizada con una posición trófica de consumidor primario, tal como se ha encontrado en organismos juveniles de M. liza en este trabajo. Pequeños organismos asociados al sedimento como microcrustáceos, anfípodos, bivalvos y gasterópodos también han sido reportados en la dieta de M. liza, en línea con los resultados isotópicos obtenidos en este trabajo (Thompson, et al, 2015). Las fuentes de materia orgánica colectadas en la Laguna Garzón incluyeron el MOP en suspensión (el cual integra al material vivo del fitoplancton y al detritus), MOS y plantas vasculares.…”
Section: Discussionunclassified
“…When the intermediate hosts are ingested by the fish (definitive host), the larvae excyst, attach to the intestinal wall and becomes sexually mature (Kennedy 2006;Rosas-Valdez, Morrone, and García-Varela 2012). The feeding studies of juveniles and subadults of M. liza within the Argentine territory recorded by Jerez and Christiansen (1987), Acha (1990) and Thompson et al (2015) indicated the presence of benthic diatoms, dinoflagellates and metazoans, mainly copepods and amphipods in the stomach content. No changes in the diet were observed with the body size.…”
Section: Habitat and Prevalence In The Definitive Hostmentioning
confidence: 97%